Latino/a children's and young adult writers on the art of storytelling - Aldama, Frederick Luis, 1969- (Pittsburgh, Pa. : University of Pittsburgh Press, 2018)
"This book is an original collection of more than thirty interviews led by Frederick Luis Aldama with Latino/a authors working in the genre."
Foreword : Magical encounters with Latino children's literature / Jamie Campbell Naidoo -- Preface : Our stories matter and we matter / Norma Elia Cantú -- Introduction : The heart and art of Latino/a young people's fiction / Frederick Luis Aldama -- The authors and artists -- Jorge Aguirre -- Malín Alegria -- Monica Brown -- Joe Cepeda -- René Colato Laínez -- Lulu Delacre -- Matt de la Peña -- Christina Diaz Gonzalez -- Angela Dominguez -- Margarita Engle -- Xavier Garza -- Diane Gonzales Bertrand -- Maya Christina Gonzalez -- Raúl Gonzalez III -- Manuel Luis Martinez -- Meg Medina -- Rhode Montijo -- Pat Mora -- Yuyi Morales -- Pam Muñoz Ryan -- Daniel José Older -- Judith Ortiz Cofer -- Ashley Hope Pérez -- Lila Quintero Weaver -- Cristy C. Road -- Rafael Rosado -- Benjamin Alire Sáenz -- Alex Sanchez -- Francisco Stork -- Carmen Tafolla -- Samuel Teer -- Duncan Tonatiuh -- Jenny Torres Sanchez -- Afterword : We all need chocolate factories and casitas on Mango Street / Belinda G. Acosta.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Hispanic American authors -- Interviews; Children's literature, American; Young adult literature, American; American literature -- Hispanic American authors; Littérature américaine -- Auteurs américains d'origine latino-américaine.; Littérature pour jeunes adultes américaine.; Littérature de jeunesse américaine.; Écrivains américains d'origine latino-américaine -- Entretiens; LITERARY CRITICISM -- American -- Hispanic American; LITERARY CRITICISM -- American -- General; LITERARY CRITICISM -- General; American literature -- Hispanic American authors; Children's literature, American; Hispanic American authors; Young adult literature, American; Interview; interviews; Interviews; Interviews; Interviews